Perfoma Mesin Sepeda Motor Empat Langkah Berbahan Bakar Premium dan Pertamax - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The Republic of Indonesian government proposes the owners of private vehicle in order to use pertamax as fuel. Premium will be consumpted specially for the public transportation. Therefore it is required research how the effect offuel used to the engine performance. This research has used a matic motor-cycle engine as testing material. This vehicle is used because matic vehicle are large applicated as private transportation. Data which are required as performance of the engine, involve power and torsion, rate offuel consumption, temperature of cylinder head cover and emission of the exhausted gas. Based on the analysis of the data, can be concluded that type of the fuel affects to the engine performance. The power, torsion and temperature of cylinder head cover of the engine which consumpted pertamax are higher than engine which consumpted premium. Rate of premium consumption is larger than rate of pertamax consumption.